Ciprofloxacin: An Overview of Uses, Mechanism of Action, and Adverse Effects - Almutairi, Bader Awadh A; Almotawa, Amjad Abdullrahman; Almutairi, Masaad Awadh Mawadh; Baabbad, Ranya Salem; Abdullah S, Alzahrani Ali; Alagedi, Hassan Shabi K; Aljaizani, Ebtisam Ali Hassan; Alahmar, Mohammed Ali; Shabi, Fatimah Ali Ahmad; Alharbi, Shaden Abdullah; Alaboudi, Ibrahim Suliman Ali; Kaabi, Ahmed Abdullah; et al. (Journal of Ecohumanism, 2024)
Background: Ciprofloxacin, a fluoroquinolone antibiotic patented in 1983 and FDA-approved in 1987, is widely used for bacterial infections. It treats urinary tract infections (UTIs), pneumonia, and more, including off-label uses like Crohn’s disease and cancer cell suppression. Aim: To provide an overview of ciprofloxacin’s uses, mechanism of action, pharmacokinetics, administration, and associated adverse effects. Methods: A comprehensive review of literature and guidelines examined ciprofloxacin’s therapeutic applications, effectiveness, resistance patterns, and patient-specific considerations. Results: Ciprofloxacin demonstrates a broad antimicrobial spectrum, primarily by inhibiting DNA replication via DNA gyrase and topoisomerase. It exhibits high tissue penetration, reaching therapeutic levels in various fluids and tissues, including CSF under inflammation. Resistance mechanisms include DNA gyrase mutations and efflux pump activity, limiting efficacy in some settings. Ciprofloxacin is effective in oral, intravenous, and topical formulations, with renal excretion as the primary elimination pathway. However, adverse effects like tendonitis, QT prolongation, neuropsychiatric events, and rare severe dermatological reactions are reported. Use in neonates, pregnancy, and breastfeeding is restricted to specific indications. Conclusion: Ciprofloxacin remains a valuable antimicrobial agent despite resistance concerns and adverse effects. Its targeted use based on infection severity, patient comorbidities, and resistance patterns ensures optimized outcomes. Further research into resistance mitigation and alternative therapies is critical to preserve its efficacy.